Trichoderma spp. no crescimento vegetal e no biocontrole de Sclerotinia slcerotiorum e de patógenos em sementes de cártamo (Carthamus tinctorius) - Oliveira, Geovana Gomez de (2007)
The cultivation of flowers is, in Brazil, very recent and little known species have a high ornamental potential, Cartamus is such a species and there are cultivars for the production of oil and as well as for ornamental pourposes. Being a recent crop in Brazil, little is known about its associated diseases, specially those that affect the seeds and the soil borne, such as white mold that causes great losses to several crops. Six experiments were conducted with the objectives of testing the reaction of the crop to isolates of Sclerotinia sclerotiorum, the biocontrol of S. sclerotiorum and of pathogens associated to the seeds, and the effect of the biocontrollers on cartamus plant growth. Isolates of the pathogen from chrisantemum, lettuce, soybean, and carrots, as well as isolates of Trichoderma sp. (ETSR 20 e TC 1.15) and comercial products of Trichoderma spp. (Agrotrich and Trichodel®) were used. In the reaction test, the cartamus crop was more severely attacked by the isolate obtained from lettuce, which when incorporated to commercial substrate did not promote the development of the disease in plant, but reduced plant growth. Trichodel® was the product that promoted the highest growth of plants when incorporated to the substrate, even in the absence of the pathogen. The product more efficient in controlling seed pathogens was Agrotrich. In the growth of seedlings, the isolates ETSR20 and TC1.15 were the best, when applied to the seeds and the latter promoted the best emergency of seeds in commercial substrate. Therefore, the Trichoderma based products can be used in the control of seed pathogens and growth promotion of cartamus plants as seed or substrate treatment. There are differences in disease severity on cartamus among isolates of S. sclerotiorum from different crops and its presence reduces the crop s growth, even in the absence of visible symptoms